Market efficiency, trading institutions and information mirages: Evidence from an experimental asset market - Andrea Morone; Simone Nuzzo (Economics and Econometrics Research Institute (EERI), 2016)
We investigate traders' behaviour in an experimental asset market where uninformed agents cannot be sure about the presence of insiders. In this framework we compare two trading institutions: the continuous double auction and the call market. The purpose of this comparison is to test which of the two trading mechanisms performs better in promoting a convergence towards the efficient equilibrium price. In a framework where the presence of insiders is neither certain nor common knowledge, inspired by Plott and Sunder (1982) and Camerer and Weigelt (1991), we first test whether a discrete time mechanism of trading, like the call market, might be able to prevent the occurrence of information mirages and promote a greater level of efficiency when no inside information is in the market. Second, we also compare the efficiency of the two trading institutions during periods when insiders are present in the market.
Keywords: D61; E02; G12; 330; Experimental Markets; Market Efficiency; Information Mirages; Trading Institutions